P. B. Blaas, Continuity and Anachronism. Parliamentary and Constitutional Development in Whig Historiography and Anti-Whig Reaction between 1890-1930 - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1983)
Recenzja: P. B. Blaas, Continuity and Anachronism. Parliamentary and Constitutional Development in Whig Historiography and Anti-Whig Reaction between 1890-1930, Martinuus Nijhoff, The Hague—Boston-London 1978, ss. XVI + 441.